1994
DOI: 10.1346/ccmn.1994.0420312
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structure and Binding Sites of Cobalt(II) Surface Complexes on Kaolinite from X-Ray Absorption Spectroscopy

Abstract: Abstract--X-ray absorption spectroscopy (XAS) was used to determine the local molecular environment of Co(II) surface complexes sorbed on three different kaolinites at ambient temperature and pressure in contact with an aqueous solution. Interatomic distances and types and numbers of backscattering atoms have been derived from analysis of the extended X-ray absorption fine structure (EXAFS). These data show that, at the lowest amounts of Co uptake on kaolinite (0.20--0.32 ~mol m-2), Co is surrounded by ~60 ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
1
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(69 citation statements)
references
References 91 publications
2
63
1
1
Order By: Relevance
“…It is generally agreed that clay is an efficient adsorbent for some heavy metals, especially for lead [12], copper [13], cadmium [14], zinc [1,5,15,16] and nickel [17]. Although kaolinite exhibits the least exchangeability, some studies have confirmed the potential of natural and modified kaolinites for the adsorption of metal ions from solutions [16,[18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally agreed that clay is an efficient adsorbent for some heavy metals, especially for lead [12], copper [13], cadmium [14], zinc [1,5,15,16] and nickel [17]. Although kaolinite exhibits the least exchangeability, some studies have confirmed the potential of natural and modified kaolinites for the adsorption of metal ions from solutions [16,[18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…20) On the other hand, extended X-ray absorption fine structure (EXAFS) revealed that Co on kaolinite formed inner-sphere surface complex at neutral pH. 21) So, it needs various experimental methods to understand adsorp-tion mechanisms. In this study, effect of ionic strength, XPS measurement, and MO calculation were applied to elucidate adsorption mechanism between Pb(II) and substrate γ -Al 2 O 3 at high pH condition.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies using EXAFS (extend X-ray absorption fine structure) have shown that heavy metals are sorbed on clay and oxide surfaces accompanied by the formation of multinuclear or polynuclear surface complexes (i.e., surface precipitate) much more frequently than previously expected based on the thermodynamical models. [5][6][7][8][9] These microscopic studies have promoted our understanding of the real sorption mechanism. EXAFS analyses of Cd species on the montmorillonite, however, have never been reported in spite of its importance for soil pollution mainly because the K-edge EXAFS requires X-rays with higher energy than 23 keV.…”
mentioning
confidence: 99%